Optical properties and oxidation resistance of different transition metals for soft X-ray and EUV applications - Mueller, Robert; Yulin, Sergiy; Naujok, Philipp; Kaiser, Norbert; Tuennermann, Andreas (Thin Solid Films, 2017)
The results of a comparative study of Ru-, Mo-, Nb- and Pd- coatings designed for grazing angle applications in the soft X-ray and extreme ultraviolet (EUV) spectrum are presented. Optical properties and temporal stability of coatings were investigated using EUV reflectometry at 13.5 nm and grazing incidence X-ray reflectometry (GIXR) with Cu-Kα radiation. Nb- and Mo-coatings showed a strong inclination to surface oxidation at ambient atmosphere leading to reflectivity losses. The Pd coating as a noble transition metal showed the highest oxidation resistance over a period of one year. The best reflective properties at 13.5 nm were achieved by Ru coatings. GIXR simulation results of the time dependent surface oxidation were used to predict the reflective properties of the studied coatings following four months of storage in an ambient atmosphere for a wide spectral range (5.0 nm–40.0 nm).
CRIS-Team Scopus Importer:2023-04-20
Keywords: EUV reflectivity; Grazing incidence EUV mirrors; Molybdenum; Niobium; Oxidation resistant; Palladium; Ruthenium; X-ray reflectometry